2001
DOI: 10.1152/jappl.2001.91.4.1730
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of alveolar epithelium measured by molecular hetastarch absorption in isolated rat lungs

Abstract: To evaluate the transport properties of the alveolar epithelium, we instilled hetastarch (Het; 6%, 10 ml, 1 - 1 x 10(4) kDa) into the trachea of isolated rat lungs and then measured the molecular distribution of Het that entered the lung perfusate from the air space over 6 h. Het transport was driven by either diffusion or an oncotic gradient. Perfusate Het had a unique, bimodal molecular weight distribution, consisting of a narrow low-molecular-weight peak at 10-15 kDa (range, 5-46 kDa) and a broad high-molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
4
12
0
Order By: Relevance
“…These other proteins for the most part would be proteins such as immunoglobulins that are larger than albumin. Thus rat, rabbit, dog, pig, and human studies provide evidence that protein clearance from the air spaces of the lung is size dependent (17,27,28,30,37,84).…”
Section: Size Dependencementioning
confidence: 97%
See 3 more Smart Citations
“…These other proteins for the most part would be proteins such as immunoglobulins that are larger than albumin. Thus rat, rabbit, dog, pig, and human studies provide evidence that protein clearance from the air spaces of the lung is size dependent (17,27,28,30,37,84).…”
Section: Size Dependencementioning
confidence: 97%
“…Bignon and colleagues (7,8) were the first of several investigators (17,46) to report that alveolar type I and type II cells contained endogenous albumin and immunoglobulins in intracellular vesicles. Micrographs of protein in vesicles demonstrate that the alveolar epithelium is capable of endocytosis of serum protein but do not establish whether the protein is transported across the epithelium, indicate the direction of transport, nor quantify how much protein is transported.…”
Section: Vesicles Vs Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous report, we characterized the transport properties of this barrier and found that molecules larger than 200 kd were able to cross it (18). In a previous report, we characterized the transport properties of this barrier and found that molecules larger than 200 kd were able to cross it (18).…”
Section: Discussionmentioning
confidence: 81%